Pengaruh Latihan Combination Of Isotonic (COI) Dan Edukasi Terhadap Pengurangan Nyeri Punggung Bawah (NPB) Pada Pekerja Laundry Di Desa Pabelan - Ardiyana, Agus Kresna; , Dwi Kurniawati, SSt.Ft, M.Kes (2016)
Background: Laundry is one type of informal businesses, which has been growing rapidly in the community. Laundry workers generally conducting drying, rinsing, lifting, folding, ironing. This can lead to musculoskeletal disorders is generally complained in the lower back. To overcome the problem of lower back pain one can do exercises Combination Of Isotonic (COI) and education. Objective: To investigate the effect of exercise Combination Of Isotonic (COI) and Education on reducing low back pain (LBP) in the laundry workers who experience lower back pain in the village Pabelan. Methods: Research using Quasi Experimental research design Pre and Post Two Group Design by comparing the two groups, namely, exercise Combination Of Isotonic (COI) and education in the form of stretching exercises m. hamstring conducted over 4 weeks with 18 respondents. Data analysis techniques in this study using the Wilcoxon's test and Mann Whitney influence to test different influences.. Result: The results of the study the effect of exercise Combination Of Isotonic (COI) and Education using Wilcoxon test. Namely, Combination Of Isotonic exercises (COI) with the results mean p = 0.007 p <0.05 can be concluded no effect on the reduction of lower back pain, and Education with the results mean p = 0.025 p> 0.05 can be concluded no influence on the decline lower back pain. As well as the results of different test exercises influence between treatment Combination Of Isotonic (COI) and Education using Mann Whitney test with the results mean p = 0.002 p <0.05 can be concluded there is a difference between the effect of combination of isotonic exercises (COI) and education to decrease back pain under. Conclusions: There is a difference between the effects of exercise Combination Of Isotonic (COI) and Education to the decrease lower back pain. Keywords: Exercise Combination Of Isotonic (COI), Education, Lower Back Pain.